Peningkatan Hasil Belajar Bahasa Indonesia melalui Penerapan Model Pembelajaran Problem Based Learning (PBL) Siswa Kelas 4 SDN 3 Mataram - Khaerunnisa, Khaerunnisa; Musahadah, Musahadah (TSAQOFAH, 2023)
This research was designed with the aim of improving student learning outcomes in Indonesian language subjects using a problem based learning model for class IV students at SDN 3 Mataram. Based on researchers' findings regarding learning, student learning outcomes at SDN Blimbing decreased. This can be seen from the results of the assessment carried out by the teacher. Only 25% of SDN Blimbing Class IV students are able to meet the KKM, while the other 75% of students have not been able to meet the specified KKM. By using the Problem Based Learning learning model, students learn to face problems in the real world to start learning. Before students learn the concept/material, students will be given a problem that must be solved. Therefore, to solve this problem students will have an awareness of the need for new knowledge that must be learned to solve the given problem. Based on the results of the research conducted, it can be concluded that using the Problem Based Learning learning model can improve the learning outcomes of class IV students at SDN 3 Mataram Kediri. This can be seen from the percentage of completion in cycle I of 60%, increasing to 85% in cycle II. Based on these conclusions, the suggestion that can be given is that teachers should look for the right method according to the material to be taught to students. Teachers should always reflect after carrying out the learning process.